Effect of stroke rate on the distribution of net mechanical power in rowing - Hofmijster, M. J.; Landman, E. H. J.; Smith, R. M.; van Soest, A. J. (Journal of Sports Sciences, 2007)
The aim of this study was to assess the effect of manipulating stroke rate on the distribution of mechanical power in rowing. Two causes of inefficient mechanical energy expenditure were identified in rowing. The ratio between power not lost at the blades and generated mechanical power and the ratio between power not lost to velocity fluctuations and mechanical power were used to quantify efficiency (e-propelling and e-velocity respectively). Subsequently, the fraction of mechanical power that contributes to the average boat velocity was calculated (e-net). For nine participants, stroke rate was manipulated between 20 and 36 strokes per minute to examine the effect on the power flow. The data were analysed using a repeated-measures analysis of variance. Results indicated that at higher stroke rates, average boat velocity, mechanical power, e-propelling, and e-net increase, whereas e-velocity decreases (P < 0.0001). The decrease in e-velocity can be explained by a larger impulse exchange between rower and boat. The increase in e-propelling can be explained because the work at the blades decreases, which in turn can be explained by a change in blade kinematics. The increase in e-net results because the increase in e-propelling is higher than the decrease in e-velocity. Our results show that the power equation is an adequate conceptual model with which to analyse rowing performance.